Factors Influencing UCI (Universal Child Immunization) Achievement in the Working Area of Technical Implementation Unit Melak Public Health Center - Mira Trisnawaty (Rifa'Institute, 2023)
Introduction: The immunization program is part of the ways for the government in prevention and breaking the spread of diseases. The target of UCI (Universal Child Immunization) at Technical Implementation Unit of Melak Public Health Center has not reached it, which is 50% in comparison to the target, 90%. Objectives: This research aims to describe the factors that contributed to the target of UCI (Universal Child Immunization) at the work area of Technical Implementation Unit of Melak Public Health Center. Method: This research was done by using an analytical observational approach of cross sectional. The sampling was non probability sampling, which was a technique that did not give the same equal chance or opportunity to the population that became a sample. Result and Discussion: There was no cause on education (?=0,76) and occupation (?=0,58) to the target of UCI (Universal Child Immunization). But there were causes on knowledge (?=0,001), behavior (?=0,02), family support (?=0,001) and medical workers support (?=0,027) for the target of UCI (Universal Child Immunization) in the work area of Technical Implementation Unit of Melak Public Health Center. Conclusion: Based on the result, it is highly recommended for Technical Implementation Unit of Melak Public Health Center to increase their communication with people about immunization, side effects, kinds of immunizations that are conducted and the contents of immunizations